THE UNIQUENESS OF MODERN RUSSIAN-LANGUAGE LITERATURE IN UZBEKISTAN - Yuldasheva Lola Kuldashevna (Bright Mind Publishing, 2025)
Modern Russian poetry in Uzbekistan has its own history, rich heritage and strong traditions. Russian-language literature in Uzbekistan is a unique phenomenon reflecting the versatility of the country's cultural landscape. It has a number of features that distinguish it from the literature of other regions.
Keywords: Russian poetry, modern literature, spiritual heritage, tradition, cultural landscape, development native language.